Application Skyline software for doping control: Method optimization, Quality control, Data screening and Validation - Hyeon-Jeong Lee; JEON, Mijin; Jung wooyeon; SEO YOON DAM; Changmin Sung; Lee Kang Mi; SON Junghyun; Eugene C. Yi; Hophil Min (2021 The 50th Anniversary Annual Meeting and International Conference of KSPST, 2021)
As prohibited chemical lists has been increased and sophisticated by every renewal for doping control, the necessity of a sensitive and accurate analysis has increased. In response to the urgent need for the high-throughput and accurate analysis, liquid chromatography with tandem mass spectrometry (LC-MS/MS) based method were actively utilized to most of the newly designated prohibited substances. However, all vendor provide data processing software which is incapable to handle other instrumental data, it is difficult to cover all doping analysis procedure, from method development to result reporting in one platform. Skyline is an open-source and vendor-neutral software invented for the method development and data process of targeted proteomics. Recently, the utilization of skyline software has been expanding to the quantitative analysis of small molecules and lipidomics. In this study, we demonstrated Skyline as a simple unifying platform for the overall doping procedures; the method optimization, data quality monitoring, discovery of suspected doping samples, method validation of new prohibited substances. In conclusion, we suggested the novel usability of Skyline software as an all-in-one platform to process overall doping control.
Keywords: Skyline; Doping control; LC-MS/MS; Quality control; Method validation